Principal results of Borrelia genotyping in Russia - E. I. Korenberg; V. V. Nefedova; I. A. Fadeyeva; N. B. Gorelova (Бюллетень сибирской медицины)
Borrelia garinii, B. afzelii (which are widespread and epidemiologically significant), B. burgdorferi s.s., B. valaisiana, B. lusi- tania, B. spilmani circulate in Russia and neighboring countries. By sequences of the rrf (5S).rrl (23S) regions of 139 primary iso- lates B. afzelii were determined seven genetic variants belonged to the subgroup VS461, and three — to the subgroup NT28. Seven alleles variants was find by sequences 246—337 pb of p66 gen from 45 isolates B. afzelii.